Techno-Economic Evaluation of Associated Gas Usage for Gas Turbine Power Generation in the Presence of Degradation & Resource Decline - Allison, Isaiah (Cranfield University, 2014)
This research examined the technical and economic feasibility of harnessing flare gas emissions from oil fields. The outcome would provide the basis for a substantial re-utilization of this waste energy due to the current practice of flaring and use it alternatively as energy for powering oil fields, rural electrification and desalination. Nigeria is used as a case study. Burning fossil fuels have grave environmental impact, amidst increasing global concerns over harmful emissions. This research addresses resource decline and suggests divestment as a partial cure. The gas turbine is subject to degradation of its components as it is used. Though several methods of assessing gas turbine degradation have been developed with varying degrees of success, no one method has addressed issues pertaining to associated gas and its effects on degradation with divestment. Simulation of two single shaft, heavy duty industrial gas turbines; and three aero-derivative industrial gas turbines of the heavy medium and light capacity ranges were carried out for varying operating conditions, to ascertain the effects of degradation when run on associated gas. Thereafter, optimizations for the best power plant engine mix and the least cost of electricity were carried out. Genetic algorithm was used to assess a population of 10,000 individuals over 500 generations; convergence was achieved for different configurations of the five study engines at discount rates of 5% and 10%, over three power ranges. The divestment pattern starts with the lightest aero-derivative industrial gas turbine; the best power plant selection was limited to the two lightest aero-derivatives in the fleet, completely ignoring the heavy engines. A techno-economic, environmental and risk assessment model comprising performance, emission, economics and risk modules was successfully developed to assess gas turbine degradation with divestment. Using this tool, it was confirmed that associated gas usage resulted in degradation of gas turbine performance, an increase in gas collection as well as operation and maintenance costs. Also there was increasingly higher creep life consumption during slow, medium and fast degradation scenarios for both engine sets. The novel technical contribution of the research work therefore is the influence of degradation on the economic use of associated gas as fuel in gas turbine power generation; and the implementation of divestment in the face of fuel decline.
Keywords: flaring; utilization; divestment; pollution; environment